An approach to maternal ancestry in a sample of Ecuadorian "mestizo" population by sequencing the control region of mtDNA. Issue 1 (December 2019) - Burgos, G.; Simão, F.; Flores-Espinoza, R.; Yepez-Santos, J.I.; Garzón-Salazar, A.; Paz-Cruz, E.; Freire-Paspuel, B.; Carvalho, E.F.; Gusmão, L.
Abstract: Mitochondrial DNA analysis has proven to be a powerful tool to study maternal inheritance among populations. It is also useful to infer geographical origin and relationships between individuals and population samples. In this study, mtDNA control region was sequenced from 54 self-declared Ecuadorian mestizos. Haplotype diversity (0.9986 +/- 0.0039) and mean number of pairwise differences (17.586303 +/- 7.933894) were high, in accordance to previous studies. Around 96% of the analyzed individuals had Native American maternal lineages. Based on genetic distances, Ecuador showed significant differences with other South American populations, except in the comparison with another sample from Ecuadorian mestizos, as expected.